LAZISMU Marketing Communication Strategy as an Integral Part of Increasing Community Independence in Medan City - Alfaruqi, Muhammad Alif; Azhar, Anang Anas; Kustiawan, Winda (Journal La Sociale, 2023)
Poverty remains a big problem in Indonesia, including in the city of Medan. According to BPS data, the percentage of poor people in Indonesia decreased from 9.57% in September 2022 to 9.36% in March 2023. This decline was also seen in North Sumatra, from 8.33% to 8.15% in the same period. LAZISMU, as a zakat institution, uses various marketing communication strategies to increase public awareness and participation in poverty alleviation programs in Medan City. The approaches used include social media, collaboration with local media, and community events such as bazaars and workshops. Philip Kotler's marketing theory is the basis for this research methodology. The research results show that the communication strategy implemented was successful in increasing public awareness and participation, although there were still obstacles related to limited funds. LAZISMU is expected to be able to develop more effective fundraising strategies and collaborate with various parties to increase the flow of funds and program sustainability.